Soluble vascular endothelial growth factor receptor 2 and prognosis in patients with chronic heart failure. (13th August 2021) - Iguchi, Moritake; Wada, Hiromichi; Shinozaki, Tsuyoshi; Suzuki, Masahiro; Ajiro, Yoichi; Matsuda, Morihiro; Koike, Akihiro; Koizumi, Tomomi; Shimizu, Masatoshi; Ono, Yujiro; Takenaka, Takashi; Sakagami, Satoru; et al.
Abstract: Aims: Endothelial cell vascular endothelial growth factor receptor 2 (VEGFR‐2) plays a pivotal role in angiogenesis, which induces physiological cardiomyocyte hypertrophy via paracrine signalling between endothelial cells and cardiomyocytes. We investigated whether a decrease in circulating soluble VEGFR‐2 (sVEGFR‐2) levels is associated with poor prognosis in patients with chronic heart failure (HF). Methods and results: We performed a multicentre prospective cohort study of 1024 consecutive patients with HF, who were admitted to hospitals due to acute decompensated HF and were stabilized after initial management. Serum levels of sVEGFR‐2 were measured at discharge. Patients were followed up over 2 years. The outcomes were cardiovascular death, all‐cause death, major adverse cardiovascular events (MACE) defined as a composite of cardiovascular death and HF hospitalization, and HF hospitalization. The mean age of the patients was 75.5 (standard deviation, 12.6) years, and 57% were male. Patients with lower sVEGFR‐2 levels were older and more likely to be female, and had greater proportions of atrial fibrillation and anaemia, and lower proportions of diabetes, dyslipidaemia, and HF with reduced ejection fraction (<40%). During the follow‐up, 113 cardiovascular deaths, 211 all‐cause deaths, 350 MACE, and 309 HF hospitalizations occurred. After adjustment for potential clinical confounders and established biomarkers [N‐terminal B‐type natriuretic peptide (NT‐proBNP), high‐sensitivity cardiac troponin I, and high‐sensitivity C‐reactive protein], a low sVEGFR‐2 level below the 25th percentile was significantly associated with cardiovascular death [hazard ratio (HR), 1.79; 95% confidence interval (CI), 1.16–2.74] and all‐cause death (HR, 1.43; 95% CI, 1.04–1.94), but not with MACE (HR, 1.11; 95% CI, 0.86–1.43) or HF hospitalization (HR, 1.03; 95% CI, 0.78–1.35). The stratified analyses revealed that a low sVEGFR‐2 level below the 25th percentile was significantly associated with cardiovascular death (HR, 1.76; 95% CI, 1.07–2.85) and all‐cause death (HR, 1.49; 95% CI, 1.03–2.15) in the high‐NT‐proBNP group (above the median), but not in the low‐NT‐proBNP group. Notably, the patients with high‐NT‐proBNP and low‐sVEGFR‐2 (below the 25th percentile) had a 2.96‐fold higher risk (95% CI, 1.56–5.85) for cardiovascular death and a 2.40‐fold higher risk (95% CI, 1.52–3.83) for all‐cause death compared with those with low‐NT‐proBNP and high‐sVEGFR‐2. Conclusions: A low sVEGFR‐2 value was independently associated with cardiovascular death and all‐cause death in patients with chronic HF. These associations were pronounced in those with high NT‐proBNP levels.